2020
DOI: 10.5755/j01.sace.27.2.25142
|View full text |Cite
|
Sign up to set email alerts
|

Current State of Building Information Modelling in the Nigerian Construction Industry

Abstract: Building Information Modelling (BIM) has been applied to various aspects of construction processes in developed countries but Nigeria is yet to realize the full potentials of BIM. It has greater relevance for the commercial and public subsectors as it enhances construction productivity. This study examines current state of BIM in the Nigerian construction industry. The study adopted quantitative research approach by eliciting primary data through questionnaire which was administered to 150 respondents, of whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 14 publications
1
29
0
Order By: Relevance
“…In sub-Saharan Nigeria (as an exemplar of a developing country), Anifowose, et al [39] indicated the adoption level of BIM as 50% while Ogunmakinde and Umeh [40] recorded a 58% level of awareness. Olanrewaju, et al [26] also reported a high level of BIM awareness at the design stage which concurs with the findings of Onungwa and Uduma-Olugu [41] where client satisfaction and drawing improvement were identified as the major reasons for BIM usage at the design stage. However, Olapade and Ekemode [42] reported that there is very low awareness of BIM implementation for facility management practices in Nigeria.…”
Section: Awareness Of Bim In the Aeco Industrysupporting
confidence: 80%
See 4 more Smart Citations
“…In sub-Saharan Nigeria (as an exemplar of a developing country), Anifowose, et al [39] indicated the adoption level of BIM as 50% while Ogunmakinde and Umeh [40] recorded a 58% level of awareness. Olanrewaju, et al [26] also reported a high level of BIM awareness at the design stage which concurs with the findings of Onungwa and Uduma-Olugu [41] where client satisfaction and drawing improvement were identified as the major reasons for BIM usage at the design stage. However, Olapade and Ekemode [42] reported that there is very low awareness of BIM implementation for facility management practices in Nigeria.…”
Section: Awareness Of Bim In the Aeco Industrysupporting
confidence: 80%
“…Conclusively, construction professionals in developing countries are becoming aware of the benefits BIM offers, and the major problem lies in implementing BIM for construction projects. For instance, Olanrewaju, et al [26] stated that only the Eko Atlantic City project has fully implemented BIM (i.e., from design to operation stage) in Nigeria.…”
Section: Awareness Of Bim In the Aeco Industrymentioning
confidence: 99%
See 3 more Smart Citations